Effect of Social Justice Mathematics on Senior Secondary School Students’ Performance in Algebraic Expressions - Age, Terungwa James; Machaba, Masilo France; Chaver, Japhet (Department of Mathematics Education University of Muhammadiyah Malang, 2025)
Mathematics education plays a crucial role in developing students’ problem-solving skills and critical thinking. However, traditional teaching methods often fail to address social inequalities, which can impact students’ engagement and performance. This study investigated the effectiveness of Social Justice Mathematics (SJM) in enhancing senior secondary school students’ performance in algebraic expressions. Conducted in Benue State, Nigeria, the research employed a quasi-experimental pretest-post-test design with non-equivalent groups. The instrument used for data collection was the Social Justice Mathematics Algebraic Expression Test (SJMAET). A pilot test was conducted with 20 students, and the instrument’s reliability was established using the Kuder-Richardson Formula 21 (K-R21), yielding a reliability coefficient of 0.86. Data analysis revealed that students in the experimental group, who were taught using Social Justice Mathematics, outperformed their counterparts in the control group who were taught using conventional method. The findings suggest that integrating social justice principles into mathematics instruction enhances students’ academic achievement and promotes an inclusive learning environment. Therefore, it is recommended that Social Justice Mathematics be adopted in teaching algebraic expressions and other mathematical concepts to foster equity, justice, and fairness in the classroom.